Tertiary Education and Prosperity: Catholic Missionaries to Luminosity in India - Amparo Castelló-Climent; Latika Chaudhary; Abhiroop Mukhopadhyay (Institute for the Study of Labor (IZA), 2015)
This paper estimates the causal impact of tertiary education on luminosity across Indian districts. We address the potential endogeneity of tertiary education using the location of Catholic missionaries in 1911 as an instrument for current tertiary education. We find Catholic missionaries have a large and positive impact on tertiary education. Catholics were not at the forefront of tertiary education in colonial India, but they established many high quality colleges following Indian independence. Controlling for a rich set of geographical and historical characteristics, we find a positive causal effect of tertiary education on development, as measured by light density at night. The findings are robust to different measures of development, and are not driven by alternative channels through which missionaries could impact current income.
Keywords: I25; N35; O15; 330; human capital; Catholic missionaries; subregional analysis